P268 The role of growth and differentiation factor 15 in smooth muscle cell proliferation in pulmonary hypertension. (12th November 2015) - Garfield, B; Shao, D; Crosby, A; Yang, P; Morrell, N; Polkey, M; Kemp, P; Wort, SJ
Abstract : Introduction: Growth and differentiation factor 15 (GDF-15) is a prognostic marker in pulmonary hypertension (PH). Its effects on endothelial cells have been documented, but its mechanism of action and role in the development of PH have not yet been fully investigated. We aimed to define the role and mechanism of action of GDF-15 in the development of PH. Methods: Rats were treated with moncrotaline (MCT) or vehicle control and euthanized after undergoing cardiovascular monitoring 4 weeks later. The expression of GDF-15 mRNA in the lung was measured by qPCR. Total GDF-15 protein levels in serum and lung were analysed by ELISA. The distribution of GDF-15 in the lung was analysed by immunohistochemistry. GDF-15 signalling in human pulmonary artery smooth muscle cells (HPASMCs) was analysed using western blot, and its role on HPASMC proliferation was measured using a cyquant assay. Results: GDF-15 mRNA and protein levels were raised in the lung homogenates of the MCT rat compared to controls (p < 0.05). Immunohistochemistry revealed GDF-15 was localised in the endothelial cells and to a lesser extent in the PASMCs of these animal. GDF-15 levels in the serum of the MCT treated rats was higher than that in those treated with vehicle control (771 ± 345 vs. 411 ± 305, p < 0.05). Serum GDF-15 was correlated with RV/LV+S weight in the MCT treated group (Pearson r = 0.66, p < 0.05). Immunohistochemistry also revealed an increase of phospho-TGFβ activated kinase 1 (TAK1) in PASMCs of the MCT rat. In HPASMCs GDF-15 (1 ng/ml) treatment resulted in an increase in proliferation over baseline at 72 h (Figure 1 ). GDF-15 was also able to induce phosphorylation of TAK1 in HPASMCs. Conclusions: GDF-15 is over-expressed in the lung vasculature of MCT rats, mimicking human disease. GDF-15 was associated with the degree of right ventricular hypertrophy in these animals. GDF-15 downstream signalling molecule phosphorylated TAK-1 is present in increased levels in the vasculature of the MCT rat. In vitro GDF-15 treatment caused proliferation of HPASMCs and activation of TAK-1. Further investigation of this pathway is required to determine its relevance to human disease.